The importance of well protected forests for the conservation genetics of West African colobine monkeys. Issue 1 (5th December 2022) - Minhós, Tânia; Borges, Filipa; Parreira, Bárbara; Oliveira, Rúben; Aleixo‐Pais, Isa; Leendertz, Fabien H.; Wittig, Roman; Fernandes, Carlos Rodríguez; Marques Silva, Guilherme Henrique Lima; Duarte, Miguel; Bruford, Michael W.; Ferreira da Silva, Maria Joana; et al.
Abstract: In tropical forests, anthropogenic activities are major drivers of the destruction and degradation of natural habitats, causing severe biodiversity loss. African colobine monkeys (Colobinae) are mainly folivore and strictly arboreal primates that require large forests to subsist, being among the most vulnerable of all nonhuman primates. The Western red colobus Piliocolobus badius and the King colobus Colobus polykomos inhabit highly fragmented West African forests, including the Cantanhez Forests National Park (CFNP) in Guinea‐Bissau. Both species are also found in the largest and best‐preserved West African forest—the Taï National Park (TNP) in Ivory Coast. Colobine monkeys are hunted for bushmeat in both protected areas, but these exhibit contrasting levels of forest fragmentation, thus offering an excellent opportunity to investigate the importance of well‐preserved forests for the maintenance of evolutionary potential in these arboreal primates. We estimated genetic diversity, population structure, and demographic history by using microsatellite loci and mitochondrial DNA. We then compared the genetic patterns of the colobines from TNP with the ones previously obtained for CFNP and found contrasting genetic patterns. Contrary to the colobines from CFNP that showed very low genetic diversity and a strong population decline, the populations in TNP still maintain high levels of genetic diversity and we found no clear signal of population decrease in Western red colobus and a limited decrease in King colobus. These results suggest larger and historically more stable populations in TNP compared to CFNP. We cannot exclude the possibility that the demographic effects resulting from the recent increase of bushmeat hunting are not yet detectable in TNP using genetic data. Nevertheless, the fact that the TNP colobus populations are highly genetically diverse and maintain large effective population sizes suggests that well‐preserved forests are crucial for the maintenance of populations, species, and probably for the evolutionary potential in colobines. Abstract : The large and continuous forest of Taï National Park provides beneficial conditions to maintain genetic diversity in still large, stationary, and well‐connected populations of colobine monkeys. Research highlights: West African colobine monkeys inhabiting forests with contrasting levels of preservation exhibit distinct population genetic patterns in terms of their genetic diversity and demographic history. The colobines from the well‐preserved forest of Taï National Park (Ivory Coast) show high levels of genetic diversity, with historically large and stable populations, contrary to the populations from the highly fragmented Cantanhez Forests National Park (Guinea‐Bissau). Despite the increase i in hunting for bushmeat consumption in the two parks, genetic data suggests that the preservation of large forests is crucial for the persistence of these primates and the maintenance of their evolutionary potential.